Formulation, Characterization, and Evaluation of Doxorubicin-loaded Cubosome as a Cytotoxic Potentiator against HCT-116 Colorectal Cancer Cells - Almoshari, Yosif; Alam, Mohammad Intakhab; Bakkari, Mohammed Ali; Salawi, Ahmad; Alshamrani, Meshal; Sabei, Fahad Y; Safhi, Awaji Y; Alamoudi, Jawaher Abdullah; Ibrahim, Ibrahim M (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Colorectal cancer (CRC) has grown to be the world’s fourth-biggest cause of cancer-related mortality. It is critical to identify more effective treatment options for it. Objectives: Doxorubicin a potent antineoplastic agent is widely used but has severe adverse effects. Therefore, our objective is to use cubosome as an efficient drug delivery system to reduce the off-target effects and increase the cytotoxic effects in CRC cells. Materials and Methods: Pluronic F127-Based Cubosomes were prepared by low energy stirring method and loaded with doxorubicin. Physicochemical characteristics were studied using X-ray diffraction, dynamic light scattering, microscopic techniques, FTIR UV spectrophotometer, and entrapment efficiency. In vitro activity of doxorubicin-loaded cubosomes was studied on HCT-116 cells. Results: The prepared cubosomes have the required nano-size and the FTIR results showed the presence of both doxorubicin and Pluronic F-127. The entrapment efficiency of doxorubicin was high too. DOX-CBs have a better cytotoxic effect and induced ROS and reduced NO levels in HCT-116 cells. Conclusion: The obtained results show that doxorubicin-loaded cubosomes can be used to increase the cytotoxic effect in CRC cells and can be used with other chemotherapeutic agents.
Keywords: Doxorubicin; HCT-116 cells; Pluronic F127; in vitro activity; Cubosomes; Entrapment efficiency